Hubungan antara Jenis Kelamin, Usia, dan Paritas terhadap Kepesertaan KB MKJP pada Akseptor KB - Nuryuliana Nuryuliana; Sulis Puspito Rini (Pusat Riset dan Inovasi Nasional, 2026)
The Family Planning Program is one of the government's efforts to control the population in Indonesia. The Long-Term Contraceptive Method (MKJP) is a type of contraception with a fairly high protection period and is used for a long time. The purpose of the study: to determine the relationship between gender, age and parity to MKJP KB participation in KB acceptors. Research method: Analytical Survey with Cross-Sectional design. Population: 1.039 KB acceptors in Poncosari Village, Srandakan in 2025, with a sample size of 1.039 KB acceptors taken using the Total Sampling technique. The results showed that 830 (79.9%) acceptors were female, 694 (66.8%) acceptors had age risk factors, 182 (17.5%) acceptors with parity >2, and 575 (55.3%) acceptors with MKJP KB participation. From the results of statistical tests: gender (p = 0.000), age (p = 0.349), parity (p = 0.000). The conclusion is that there is a relationship between gender and parity on MKJP KB participation in KB acceptors; there is no relationship between age on MKJP KB participation in KB acceptors. Thus, gender and parity factors are important determinants in MKJP KB participation, so they need to be considered in the planning and implementation of the Family Planning program.